Migrant Entrepreneurship and New Urban Economic Opportunities - Peter Nijkamp; Mediha Sahin; Tüzin Baycan-Levent (Tinbergen Institute, 2009)
Nowadays, migrants form a significant share of the urban population, and their business is critical for urban economic growth. This paper addresses the key factors determining the position of migrant entrepreneurs in the urban economy in the Netherlands. In order to develop a solid assessment of CSFs for migrant entrepreneurs, and to understand business performance in a competitive urban environment, this study will investigate the entrepreneurial behaviour of migrants in Dutch cities from a micro-economic perspective by paying attention to the entrepreneurial behaviour of migrants, the role of their social networks, and the innovative potential of new growth markets in a city. Our research employs a comparative statistical analysis of empirical findings in order to map out opportunities, success conditions and bottlenecks for migrant entrepreneurs. Given our largely categorical database, we will employ a qualitative causal pattern recognition technique, viz. rough set analysis, to systematically assess the conditions for successful entrepreneurship of migrants.
Keywords: J61; L26; 330; Migrant entrepreneurship; rough set analysis; critical success factors; categorical pattern recognition analysis; Migranten; Entrepreneurship-Ansatz; Kommunale Wirtschaftsentwicklung; Erfolgsfaktor; Unternehmenserfolg; Niederlande